Proceedings of the Companion Publication of the 2015 Annual Conference on Genetic and Evolutionary Computation 2015
DOI: 10.1145/2739482.2768465
|View full text |Cite
|
Sign up to set email alerts
|

Designing and Modeling a Browser-Based DistributedEvolutionary Computation System

Abstract: Web browsers have scaled from simple page-rendering engines to operating systems that include most services the lower OS layer has, with the added facility that applications can be run by just visiting a web page. In this paper we will describe the front and back end of a distributed evolutionary computation system that uses the browser's capabilities of running programs written in JavaScript. We will focus on two different aspects of volunteer computing: first, the pragmatic: where to find those resources, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…NodIO [59][60] was created as a framework for creating experiments solving problems using evolutionary/genetic algorithms. The project site's visitors see a HTML page showing graphs, links and information about an experiment, and running workers.…”
Section: The Third Generation: Fast and The Furiously Multithreadingmentioning
confidence: 99%
See 2 more Smart Citations
“…NodIO [59][60] was created as a framework for creating experiments solving problems using evolutionary/genetic algorithms. The project site's visitors see a HTML page showing graphs, links and information about an experiment, and running workers.…”
Section: The Third Generation: Fast and The Furiously Multithreadingmentioning
confidence: 99%
“…Fox et al [30] identified environmental protection, weather forecasting and economic growth projection as kind of problems which potentially may attract many volunteers. Whatever the problem is, its results should be freely accessible as both an ethical way to thank the public and as a way to popularize the project and attract more volunteers [59].…”
Section: Recruiting and Keeping The Volunteersmentioning
confidence: 99%
See 1 more Smart Citation
“…60 At the time, the required HTML5 canvas element for drawing graphics was not widely supported by browsers, but the situation has now greatly improved, as weʼll see in the next section. 66 In 2010, the Swedish creative studio B-Reel Creative, in collaboration with Google Creative Labs and the American music video director Chris Milk, designed a groundbreaking web-based video called The Wilderness Downtown. 67 The project, a Grand Prix winner at the 2011 Cannes Advertising Awards and recipient of a host of other awards, 68 was a trailblazer for many of the possibilities opened up by open web technologies, including HTML5 video, audio, and canvas.…”
Section: Native Html and Http Technologiesmentioning
confidence: 99%
“…These include studies employing popular cloud-based storage services (specifically, Dropbox 136 and SugarSync 137 ) [67], and others implementing JavaScript-based evolutionary algorithms [66,65]. Other work has studied how the performance of different architectures of web-based evolutionary algorithms is affected when client nodes join and leave the cluster during an evolutionary run [51].…”
Section: Other Workmentioning
confidence: 99%